A level playing field: An optimal weighting scheme of dismissal protection characteristics - Michael Kind (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
In the case of collective redundancies, employers are forced to regard certain characteristics when deciding who is going to be dismissed. This paper develops a procedure to derive an empirical based weighting scheme between the characteristics relevant for this selection (age, disability, dependencies and tenure). First, panel data from the German Socio-Economic Panel (SOEP) for the years 1991-2010 is used to estimate, conditional on the existence of dismissal protection, the relationships of the four characteristics with respect to reemployment probabilities and the quality of the new job (measured in terms of wage). Second, the individual valuation of the two outcomes is compared applying a life satisfaction analysis. Finally, based on the empirical results a weighting scheme for the characteristics is proposed, which serves as an evidence based guideline for employers, employees and unions in the process of collective redundancies.
Keywords: J63; J64; 330; dismissal protection; reemployment probability; wage hit